AN ALGORITHM FOR APPLYING STATISTICAL METHODS IN THE IDENTIFICATION OF SUBSPECIES AND HYBRIDS OF PANTHERA PARDUS - O. Chernova; T. T. Perfiova; A. Kiladze; P. Sorokin (Теория и практика судебной экспертизы, 2015)
The study focused on the methodological aspect of applying multivariate statistics in the forensic biological analysis of mammalian hair, using samples from subspecies and hybrids of leopard.